Somewhere among - Donwerth-Chikamatsu, Annie (New York : Scholastic, 2016)
Eleven-year-old Emma's life in Tokyo changes for the worse when she and her American mother, who is pregnant, must move in with her Japanese grandmother the summer before 9/11 changes the world.
O
"A Caitlyn Dlouhy Book."
b
b
Keywords: Family life -- Japan -- Fiction; Belonging -- Fiction; Racially mixed people -- Fiction; Grandmothers -- Fiction; Pregnancy -- Fiction; September 11 Terrorist Attacks, 2001 -- Fiction; Novels in verse; JUVENILE FICTION / People & Places / Asia; JUVENILE FICTION / Stories in Verse; JUVENILE FICTION / Family / New Baby